مشكلات تطبيق التعليم عن بعد من وجهة نظر الطلبة - سعيد, ايمان (جامعة الوادي - University of Eloued, 2021)
Study summary in English: The study aimed to reveal the problems of applying distance education from the perspective of students in the first year of social sciences. The descriptive exploratory approach was relied upon. As for the data collection tools, the questionnaire was relied upon, which included 29 questions, and the applied study was conducted on a random sample of 120 A first-year social science student at Hama Lakhdar University in the Valley, and the following results have been reached: -The most important problems of applying distance education from the perspective of first-year students of social sciences, and the most important of them in the first field were difficulties related to experience in using distance education and poor experience in using computers and the Internet, as well as in the second field, difficulties related to infrastructure and technical support in lecture halls, and from Among them is the difficulty of implementing video lectures between professors and students. With regard to the third area, the difficulties are related to students. I found some difficulties represented in the lack of awareness of the importance of distance education and the low language abilities necessary in dealing with distance education, as well as the students’ preoccupation with sites that have nothing to do with distance education. -There are no statistically significant differences between the averages of students, responses to the problems of applying distance education due to the gender variable (male-female).
دراسة تطبيقية على عينة من الطلبة سنة أولى جذع مشترك علوم الاجتماعية بجامعة الشهيد حمه لخضر بالوادي
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: التعليم عن بعد; L'enseignement à distance; Distance Learning